Child Migration and Educational Inclusion, a Topic to Be Addressed for the Development of Comprehensive Care Approaches and Policies in Latin America - Sánchez-Mojica, John Fredy (2021)
Objective: To reflect on how national governments implement the commitments acquired to favor the development of educational inclusion to face the problem of child migration, proposing alternatives responding to the needs of the affected population. Methodology. This paper provides a review of the literature on the theme of child migration and educational inclusion. A total of 29 articles were selected, published between 2004 and 2020, mainly in the Latin American region. All the articles conceptualize the issue of educational inclusion, analyze the problem of quality education due to the development of migration, and propose strategies to face this problem. At the beginning of the research, it is evident that there is a low production concerning this theme, so it is evaluated from three different categories: (1) educational inclusion, (2) migration and inclusion, and (3) child migration and educational inclusion. These categories were identified progressively and helped to delimit a historical overview of the development of concepts. Results. The results show that the concept of educational inclusion applied to the child migrant population has been poorly developed, regardless of interesting reflections that account for a theoretical transformation that should be explored with the proposal to contribute to the design of public policy and substantive transformations. Conclusions. The specific conclusions suggest that this transformation not only has an impact exclusively on migrant children but also on their classmates, their teachers, their environment, their family, among others, so this reflection process is required to understand inclusion in a multicultural context.